Dark Energy or just Energy? - Nick Markov (Zenodo, 2019)
This letter hypothesizes that matter expands proportionally with space. The expansion is quantized at the particle level. Every force arises from a specific scaling distortion. In this sense, the universal expansion can be also causing gravity instead of opposing it. The new perspective works without dark matter, extra dimensions, big bang, great attractor, and does not require changes to the established laws of physics. Six different approaches are proposed to validate the hypothesis at the macro and micro levels.
Is gravity a group phenomenon caused by a relativistic delay due to the limited speed of quantum interactions within a given mass? Another hint pointing in this direction was added to this revision. The escape velocity magnitude is similar to the average pressure wave velocity within the Earth. P-waves cross our planet in 16 min - 20 min. Earth diameter is 12,742 km. Therefore the P-waves propagate at 10.6 km/s – 13.3 km/s, while the gravitational time dilation is based on the escape velocity of 11.2 km/s.
Keywords: Universal expansion; Gravity